Posttransciptional gene regulation : RNA processing in - Wu, Jane (Wiley-Blackwell, 2013)
Reflecting the rapid progress in the field, the book presents the current understanding of molecular mechanisms of post-transcriptional gene regulation thereby focusing on RNA processing mechanisms in eucaryotic cells. With chapters on mechanisms as RNA splicing, RNA interference, MicroRNAs, RNA editing and others, the book also discusses the critical role of RNA processing for the pathogenesis of a wide range of human diseases. The interdisciplinary importance of the topic makes the title a useful resource for a wide reader group in science, clinics as well as pharmaceutical industry